COMPARISON OF EFFECTIVENESS OF HOME-BASED DONOR ACTIVATION FOCUSED REHABILITATION APPROACH (DAFRA) AND INSTITUTIONAL BASED REHABILITATION FOLLOWING UPPER LIMB NERVE TRANSFERS IN REGAINING FUNCTION - Saleem, Nousheen; Aslam, Ayesha; Ali, Ahmed; Aman, Sameena; Mehmood , Mehwish; Feroz, Hira; Rizwan, Samia; Tariq, Nadiya; Ikram, Anum; Hummayoun, Shanzay (Journal of Ayub Medical College Abbottabad, 2025)
Introduction: Brachial Plexus injuries cause devastating impact on quality of life. Management of these injuries include surgical intervention of nerve transfer and then rehabilitation post surgically to maximize the functional outcome. Rehabilitation can be institutional-based or donor activation focused rehabilitation approach. (DAFRA). Purpose of the study was to evaluate and compare the results of home-based donor activation focused rehabilitation approach and institutional-based rehabilitation following nerve transfers in upper limb. Methods: It is a comparative study which was conducted from January 2015 to December 2022. Patients were divided into two groups, Group A included patients who had a home-based exercise program that is DAFRA and Group B consisted of patients who underwent institutional based rehabilitation. After 3 weeks of surgery rehabilitation was started and the gain in muscle strength was recorded using Medical Research Council’s (MCR) grading for muscle strength at 18 months was compared in both groups. Results: Total 23 patients under went 41 nerve transfers. Group A had 16 patients with 27 nerve transfers and group B had 7 patients with 14 nerve transfers. Mean age of the patients was 35.13±18.6 years in Group A while 36.57±15.62 years in the Group B. Mean gain in muscle strength in home-based DAFRA was 3.96±0.922 (out of 5) and that in institutional based rehabilitation was 3.71±0.726 (out of 5). Conclusion: It can be concluded that significant improvements can be gained by vigorous rehabilitation regimens either in institutions or at home targeting donor nerves. Home based DAFRA exercises are equally effective as institutional based rehabilitation.